Effectiveness of TES and rTMS for the Treatment of Insomnia: Meta-Analysis and Meta-Regression of Randomized Sham-Controlled Trials - Ma, Haixia; Lin, Jingxia; He, Jiali; Lo, Dilys Hoi Ting; Tsang, Hector W. H. (Frontiers in Psychiatry, 2021)
Objectives: Transcranial electric stimulation (TES) and repetitive transcranial magnetic stimulation (rTMS) have experienced significant development in treating insomnia. This review aims to examine the effectiveness of randomized sham-controlled trials of TES and rTMS in improving insomnia and examine potential moderators associated with the effect of the treatment. Methods: Nine electronic databases were searched for studies comparing the effects of TES/rTMS with sham group on insomnia from the inception of these databases to 25 June 2021, namely the Medline, Embase, PsycINFO, CINAHL, Cochrane Library, Web of Science, PubMed, ProQuest Dissertation & Thesis, and CNKI. Meta-analyses were conducted to examine the effect of TES and rTMS in treating insomnia. Univariate meta-regression was performed to explore potential treatment moderators that may influence the pooled results. Risk of bias was assessed by using the Cochrane Risk of Bias Tool. Results: A total of 16 TES studies and 27 rTMS studies were included in this review. The pooled results indicated that there was no significant difference between TES group and sham group in improving object measures of sleep. rTMS was superior to its sham group in improving sleep efficiency (SE), total sleep time (TST), sleep onset latency (SOL), WASO (wake up after sleep onset), and number of awakenings (NA) (all p < 0.05). Both TES and rTMS were superior to their sham counterparts in improving sleep quality measured by the Pittsburgh Sleep Quality Index (PSQI) at the post intervention. The weighted mean difference (WMD) for TES and Rtms were -1.17 (95% CI -1.98, -0.36) and -4.08 (95% CI -4.86, -3.30), respectively. Gender, total treatment sessions, number of pulses per session, and length of treatment per session were associated with rTMS efficacy. No significant relationship was observed between TES efficacy and the stimulation parameters. Conclusions: It seems that TES and rTMS have a chance to play a decisive role in the therapy of insomnia. Possible dose-dependent and gender difference effects of rTMS are suggested.